EFFECT OF PLANTING DATES AND NITROGEN LEVELS ON GROWTH, FODDER YIELDS OF BLUEPANIC Panicum antidotale Retz. - Abdul Wahid, Mohammed Abdul-Raza; Al-Rifa'i, Shaimaa Ibrahim (Diyala Agricultural Sciences Journal, 2020)
The experiment carried out in Al- Muthanna University research (800 m away from Samawah City Center) during the summer seasons 2017-2018 and 2018-2019 to study the effect of three planting dates 5thApril, 20thApril and 5th May and five levels of nitrogen fertilization (0, 100, 150, 200 and 250 kg N ha-1 ) and their interaction on growth, green forage yield of Panicum antidotale Retz.. Ten cutting managements were taken. The experiment was designed in a randomized complete blocks (RCBD) in a Factorial arrangement with three replications. The results showed that sowing dates on 5 th May gave the highest mean of plant height at the 4 th, 5th, 6th,7th,8th cuts respectively 138.68, 147.00, 139.00, 146.50,149.50 cm, number of tillers 303.90 ,317.70,479.80 ,543.40 ,421.40, 451.30, 483.20, 475.80 ,483.20 tiller m-2 for the 1st , 7 nd, 3rd, 4th, 6th, 7th, 8th,9th,10th cuts respectively, green forage yield 31.83, 36.55,44.51, 37.59, 50.91, 53.14,35.05 t ha-1 for the 7 nd, 4th , 5 th,6th, 7th, 8th,10th cuts respectively. The results indicated a significant superiority in the level of fertilizer 758 kg N ha-1 on plant height 138.3 ,136.2 ,144.3 ,143.6,147.4,140.0 ,151.6 ,153.5 ,142.0 ,139.2,149.2 ,145.3 139.0,126.7 cm for the all cutting respectively, number of tillers 536.50,459.00,434.50 tiller m-2 for the 4th , 7 th,8th cuts respectively, green forage yield 25.79 ,40.62 ,33.68 ,50.83 ,57.52 ,55.46 ,45.37 ,37.33 t ha-1 for the 1st, 3rd , 4th, 5th, 7th, 8th, 9 th 10th cuts respectively.